DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DE NANOPARTÍCULAS DE PLGA REVESTIDAS COM QUITOSANA PARA ADMINISTRAÇÃO ORAL DE ÁCIDO FERÚLICO - Lima, Isabela Angeli de (2017)
Trans ferulic acid (FA) is a natural compound that belongs to phenolic acids and presents high antioxidant and cytoprotective activity. It acts as free radical scavenger and in the activation of cellular response. However, its application from conventional oral dosage forms is restricted, mainly due to its low solubility and permeability in aqueous media. For this reason, the delivery of this compound by modified release systems has been investigated. In this work, nanoparticles of poly (lactic-co-glycolic acid) (PLGA) coated with chitosan (CS) containing ferulic acid (FA) for oral administration were developed, characterized and in vitro evaluated for the antioxidant activity, cytotoxicity against normal cells (erythrocytes and Caco-2 cells) and tumor cells line (B16-F10 and HeLa). Also, the nanoparticles permeability through intestinal cell monolayers was carried out. Initially, a simple and efficient method for the FA quantification in the nanoparticles by reverse phase high performance liquid chromatography coupled to photodiode array detection was developed and validated. Nanoparticles were sucessfully obtained by emulsion evaporation technique, presenting a spherical or slightly oval shape, mean diameter of about 240 nm, low polydispersity index, zeta potential of +32 mV and 50% of encapsulation efficiency. FTIR, XRD and DSC-TGA analyses suggested the FA interaction with the polymeric matrix and drug amorphization. The suspended nanoparticles were physical and chemically stable for 6 months. The FA in vitro release in phosphate buffered saline (pH 7.4) demonstrated a biphasic profile, guided by the diffusion process. In 120 h of assay, about 28% of the encapsulated FA was released into the medium. For the FA release in simulated gastrointestinal fluids, the physical integrity and stability of nanoparticles in these media was presented. Furthermore, low cellular toxicity was demonstrated against erythrocytes and Caco-2 cells. In the HOCl scaveging activity, the nanoparticles presented the same efficacy of free drug at 96 h of assay. After 48 h, the nanoparticles were able to reduce the cell viability of B16-F10 and HeLa cells in 63% and 33%, respectively. In the intestinal permeability study, the encapsulated FA exhibited a permeation of 6% through the Caco-2 monolayer and of 20% through the Caco-2/HT29-MTX/Raji B co-culture within 3 h. Therefore, PLGA-CS nanoparticles showed be potential carriers for the controlled release of FA for oral administration, and may be used in anti-tumor and chemopreventive treatments and in oxidative stress-based diseases.